Risankizumab as maintenance therapy for moderately to severely active Crohn's disease: results from the multicentre, randomised, double-blind, placebo-controlled, withdrawal phase 3 FORTIFY maintenance trial. Issue 10340 (28th May 2022) - Ferrante, Marc; Panaccione, Remo; Baert, Filip; Bossuyt, Peter; Colombel, Jean-Frederic; Danese, Silvio; Dubinsky, Marla; Feagan, Brian G; Hisamatsu, Tadakazu; Lim, Allen; Lindsay, James O; Loftus, Edward V; et al.
Summary: Background: There is a great unmet need for new therapeutics with novel mechanisms of action for patients with Crohn's disease. The ADVANCE and MOTIVATE studies showed that intravenous risankizumab, a selective p19 anti-interleukin (IL)-23 antibody, was efficacious and well tolerated as induction therapy. Here, we report the efficacy and safety of subcutaneous risankizumab as maintenance therapy. Methods: FORTIFY is a phase 3, multicentre, randomised, double-blind, placebo-controlled, maintenance withdrawal study across 273 clinical centres in 44 countries across North and South America, Europe, Oceania, Africa, and the Asia-Pacific region that enrolled participants with clinical response to risankizumab in the ADVANCE or MOTIVATE induction studies. Patients in ADVANCE or MOTIVATE were aged 16–80 years with moderately to severely active Crohn's disease. Patients in the FORTIFY substudy 1 were randomly assigned again (1:1:1) to receive either subcutaneous risankizumab 180 mg, subcutaneous risankizumab 360 mg, or withdrawal from risankizumab to receive subcutaneous placebo (herein referred to as withdrawal [subcutaneous placebo]). Treatment was given every 8 weeks. Patients were stratified by induction dose, post-induction endoscopic response, and clinical remission status. Patients, investigators, and study personnel were masked to treatment assignments. Week 52 co-primary endpoints were clinical remission (Crohn's disease activity index [CDAI] in the US protocol, or stool frequency and abdominal pain score in the non-US protocol) and endoscopic response in patients who received at least one dose of study drug during the 52-week maintenance period. Safety was assessed in patients receiving at least one dose of study medication. This study is registered with ClinicalTrials.gov, NCT03105102 . Findings: 712 patients were initially assessed and, between April 9, 2018, and April 24, 2020, 542 patients were randomly assigned to either the risankizumab 180 mg group (n=179), the risankizumab 360 mg group (n=179), or the placebo group (n=184). Greater clinical remission and endoscopic response rates were reached with 360 mg risankizumab versus placebo (CDAI clinical remission was reached in 74 (52%) of 141 patients vs 67 (41%) of 164 patients, adjusted difference 15% [95% CI 5–24]; stool frequency and abdominal pain score clinical remission was reached in 73 (52%) of 141 vs 65 (40%) of 164, adjusted difference 15% [5–25]; endoscopic response 66 (47%) of 141 patients vs 36 (22%) of 164 patients, adjusted difference 28% [19–37]). Higher rates of CDAI clinical remission and endoscopic response (but not stool frequency and abdominal pain score clinical remission [p=0·124]) were also reached with risankizumab 180 mg versus withdrawal (subcutaneous placebo; CDAI clinical remission reached in 87 [55%] of 157 patients, adjusted difference 15% [95% CI 5–24]; endoscopic response 74 [47%] of 157, adjusted difference 26% [17–35]). Results for more stringent endoscopic and composite endpoints and inflammatory biomarkers were consistent with a dose–response relationship. Maintenance treatment was well tolerated. Adverse event rates were similar among groups, and the most frequently reported adverse events in all treatment groups were worsening Crohn's disease, arthralgia, and headache. Interpretation: Subcutaneous risankizumab is a safe and efficacious treatment for maintenance of remission in patients with moderately to severely active Crohn's disease and offers a new therapeutic option for a broad range of patients by meeting endpoints that might change the future course of disease. Funding: AbbVie.